PENDIDIKAN LINGKUNGAN HIDUP BERBASIS PENDIDIKAN ISLAM SEBUAH PARADIGMA INTEGRATIF - Umar (AN NUR: Jurnal Studi Islam, 2013)
The environmental issue which happens in this era is so bad, fluctuative, and continuity, so the effect is to human’s life system. The environmental issue of global ecology is about moral globalitation. Environmental education at least has a great constribution in the efford to impede the decline of the environmental quality through an integrative Islamic education. Islam has already defined the constraints and concepts of education based on environment. Thus, two main strategies should be wholl integrated environmental education and Islamic education. Integrative education can be able people either individual or in group realize the existence of the importance of maintaining the environment by promoting solutions based on Islamic principles.